Tungguk Tembakau Traditional Ceremony in Boyolali Regency: Cultural Values and Simbolic Meanings - Alifia Nur Aini; Sumarwati, Sumarwati; Ulya, Chafit (BAHASTRA, 2026)
Tungguk Tembakau is a traditional ceremony marking the beginning of the tobacco harvest in Senden Village, Boyolali, as an expression of gratitude to God. Although it is carried out regularly, a deep understanding of its value and symbolic meaning has begun to fade among the community. This study aims to explore the cultural values and symbolic meanings of the Tungguk Tembakau tradition. Using qualitative methods, this study integrates James Spradley's ethnographic approach and Roland Barthes' semiotics. Data were collected through participant observation, in-depth interviews with purposively selected informants (traditional leaders, village officials, farmers), and documentation. Data analysis was conducted through two systematic approaches: first, ethnographic analysis (domain, taxonomy, components, and cultural themes) to reveal value orientations; second, semiotic analysis through a two-stage system of signification (denotation and connotation/myth) to dissect ritual artifacts. Data validity was ensured through triangulation of sources and methods. The results of the study reveal four cultural value orientations: (1) The relationship between humans and God as an expression of gratitude; (2) The relationship between humans and nature, reflecting agricultural cosmology and ecological dependence; (3) Interpersonal relationships through mutual solidarity; and (4) The relationship between humans and time through respect for ancestors. Semiotically, each procession is a symbolic language. The picking of 16 tobacco leaves symbolizes obedience to the cosmic order, while the parade functions as a ritual to ward off evil spirits. Various forms of gunungan and tamping offerings connote prosperity, soil fertility, and collective hopes for a smooth seasonal transition. This study concludes that Tungguk Tembakau is a complex symbolic system that strengthens cultural identity and maintains harmony between spirituality and the social order of agrarian communities.